2007
DOI: 10.1111/j.1447-0756.2007.00660.x
|View full text |Cite
|
Sign up to set email alerts
|

Relaparotomy after cesarean delivery: Experience from an Indian teaching hospital

Abstract: Repeat laparotomy within 6 weeks of cesarean delivery was required following 1 in 300 cases done in an Indian teaching hospital. The majority of these were preventable and could have been avoided if adequate attention had been paid at the time of the primary surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
59
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 10 publications
9
59
1
Order By: Relevance
“…Seal et al [3] in their study found that the interval between the initial surgery and relaparotomy is one of the most significant factors influencing the outcome. In the present study, the cases requiring relaparotomy within 24 h were due to haemorrhagic complications.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Seal et al [3] in their study found that the interval between the initial surgery and relaparotomy is one of the most significant factors influencing the outcome. In the present study, the cases requiring relaparotomy within 24 h were due to haemorrhagic complications.…”
Section: Discussionmentioning
confidence: 98%
“…It is a major surgery, and morbidity is higher as compared to vaginal delivery [2]. One of the rare but serious post-caesarean morbidities is a relaparotomy so much so that it is considered to be a near-miss mortality [3]. The purpose of a relaparotomy is to manage complications of the previous surgery such as secure haemostasis, manage intraabdominal infection or sepsis, relieve intestinal obstruction and maintain intestinal continuity or to carry out delayed curative surgery.…”
Section: Introductionmentioning
confidence: 99%
“…So, hysterectomy incidence was more in our study compare to Indian study (10.61%). 6 Interesting finding was that all secondary PPH needed hysterectomy. Indian study showed that 11 cases needed third relaparotomy following conservative surgery in second laparotomy.…”
Section: Discussionmentioning
confidence: 99%
“…1,4,12,13 In some studies, the incidence was similar to ours with 39.8% caused while in other studies it was as high as 70.8% of the cases. 10 Although there was no indication in literature of the right time for the resurgery, it is common consensus that the earlier it is diagnosed, the better.…”
Section: Discussionmentioning
confidence: 48%
“…Erdal et al reported an incidence of 0.80% 10 , while in another study in Ghana the incidence was 0.7% 11 , and 0.33% and 1.56% in studies from India. 4,13 Intraperitoneal bleeding and was the most common cause (38.9%) of a reoperation which normally originated form uterine, epigastric or hypogastric arteries, followed by rectus sheath hematoma (25%) and sepsis (11.1%).…”
Section: Discussionmentioning
confidence: 99%